TEACHERS' PERCEPTIONS OF THE CHARACTER OF LOVE FOR THE COUNTRY IN ELEMENTARY SCHOOLS - Ratno Saputra; Sapriya Sapriya (Jurnal Cakrawala Pendas, 2024)
The cultivation of the character of love for the country is necessary in 4.0 era as a means of strengthening the identity of the nation. The character of love for the country can be fostered from an early age through education.  Teachers are at the forefront of education and their direct interactions with students are crucial. Teachers' perceptions of the character of love for country influence strategies in the learning process. This study aims to explain teachers' perceptions of the character of patriotism at the primary school level. This research follows a qualitative approach with a descriptive element. Data collection was conducted using interviews, observation and documentation. This research involved four teachers, consisting of two class teachers and two subject teachers, in one cluster in West Bandung Regency. The results showed an understanding related to the character of love for the country. The learning process made more use of local products and local culture as learning resources that are close to the daily lives of students. The cultivation of the love for the country's character is carried out in an integrated manner through both the intracurricular, co-curricular, and extracurricular paths. It can be concluded that there is a positive perception that aligns with the character of patriotism, which is demonstrated by the same comprehension of the ideas and strategies implemented.